2014
DOI: 10.1016/j.ymgmr.2014.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Fabry disease: Evidence for a regional founder effect of the GLA gene mutation 30delG in Brazilian patients

Abstract: The Fabry disease is caused by mutations in the gene (GLA) that encodes the enzyme α-galactosidase A (α-Gal A). More than 500 pathologic variants of GLA have already been described, most of them are family-specific. In southern Brazil, a frequent single-base deletion (GLA 30delG) was identified among four families that do not recognize any common ancestral. In order to investigate the history of this mutation (investigate the founder effect, estimate the mutation age and the most likely source), six gene-flank… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Most of the GLA gene variants (identified by us) are specific to single families, which in general is a typical feature of X-linked diseases, and FD in particular [34]. Only 17 (16.4%) GLA variants were identified in two or more families with FD, while each of the remaining variants was detected in members of the same family.…”
Section: Resultsmentioning
confidence: 85%
“…Most of the GLA gene variants (identified by us) are specific to single families, which in general is a typical feature of X-linked diseases, and FD in particular [34]. Only 17 (16.4%) GLA variants were identified in two or more families with FD, while each of the remaining variants was detected in members of the same family.…”
Section: Resultsmentioning
confidence: 85%
“…This finding can be attributed to founder effects because this mutation was present in a small number of individuals from a large population due to low genetic variation (Morrone et al, 2014). Moreover, it has been reported that other genetic disorders with low worldwide prevalence are more frequent in some ethnic groups or populations with high consanguinity rates (de Alencar et al, 2014;Fiore et al, 2011;Kirov et al, 2019). The increase in inbreeding and increased sensitivity to genetic drift occurs when a new population is established by a small number of individuals (Kato et al, 1997;Wood et al, 2013;Yamada et al, 1998).…”
Section: Mps Is Characterized By Various Mutations In the Galns Genementioning
confidence: 99%